1974
DOI: 10.1002/cber.19741070831
|View full text |Cite
|
Sign up to set email alerts
|

185 Re‐ und 187 Re‐NQR‐Untersuchungen an Trimethylsilyl‐ und Trimethylgermanyl‐perrhenat

Abstract: Eingegangen a m 25. Marz 1974 In den NQR-Spektren von polykristallinem (CH3)3SiOReq und (CH,)jGeOReO, wurden alle erwarteten Frequenzubergange q(+ fund *87Re aufgefunden und zur Bestimmung der Quadrupol-Kopplungskonstanten und des Asymmetrieparameters ausgewertet. Die erhaltenen g r o k n Werte fur eZqQ/h und q weisen eine direkte kovalente Bindung der metallorganischen Reste mit dem Perrhenat-Ion nach. Die Elementarzellen der Kristalle enthalten alle Re-Atome in iiquivalenten Positionen. IESRe-and 187Re-NQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…21 Detailed 185,187 Re NQR measurements have confirmed that in this ester the ReO 4 tetrahedron is indeed strongly distorted. 22 Similar overall characteristics were found for organogermanium, -tin and -indium perrhenates. [23][24][25][26][27] The combination of perrhenate with the heavy coinage metals, Ag and Au, is poorly presented in the literature.…”
Section: The Perrhenate Anion Reosupporting
confidence: 60%
“…21 Detailed 185,187 Re NQR measurements have confirmed that in this ester the ReO 4 tetrahedron is indeed strongly distorted. 22 Similar overall characteristics were found for organogermanium, -tin and -indium perrhenates. [23][24][25][26][27] The combination of perrhenate with the heavy coinage metals, Ag and Au, is poorly presented in the literature.…”
Section: The Perrhenate Anion Reosupporting
confidence: 60%
“…The crystal structure of the trimethylsilyl compound ( R = Me) has been determined [22] and shown to have a conventional ester structure with the Si atom attached specifically to one of the oxygen atoms in an angular array. This covalent bonding has also been confirmed by 185,187 Re NQR spectroscopy studies which showed a high asymmetry parameter η for the Re atom, while for alkali perrhenates with largely undistorted ReO 4 − tetrahedra the η value deviates only slightly from zero [23]. Similar characteristics have later been found for the corresponding germanium [24] and tin compounds [25,26], the latter being aggregated through an increase in the coordination number of the tin atoms and with the ReO 4 units functioning as bridging units employing two of their four oxygen atoms.…”
Section: Introductionsupporting
confidence: 54%
“…According to Mooberry, Spiess and Sheline [8] the orientational change of the principal axes of the EFG-tensors q ik is the reason for this remarkable behaviour. Schmidbaur, Koth and Burkert [11,12] observed similar phenomena of the 185 Re and ,87 Re NQR transitions in the compound (CH 3 ) 3 Ge0Re0 3 due to the same effect.…”
Section: Anomalous Temperature Coefficientsmentioning
confidence: 77%
“…(a) the breakdown of d n -p n backbonding [3,4] (b) the occurrence [5] of sufficiently large negative pressure coefficients (9v/9p) T (c) charge transfer from n-to a-orbitals of adjacent atoms [6, 7] (d) continuous orientational change of the principal axes system of the electric field gradient (EFG) tensors q ik [8][9][10][11][12] (e) influence of reorientational motions [13 -18].…”
Section: Introductionmentioning
confidence: 99%